2000
DOI: 10.1093/qjmed/93.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for central nervous system involvement in systemic lupus erythematosus

Abstract: We investigated risk factors for central nervous system (CNS) involvement in systemic lupus erythematosus (SLE), in 32 such patients individually matched 1 : 3 to 96 control SLE patients without CNS events. Univariate analysis showed that CNS involvement was significantly associated with the antiphospholipid syndrome (APS) as well as its features: arterial thrombosis, recurrent fetal loss, livedo reticularis and IgG anticardiolipin (aCL) antibodies in high titres. Other potential associations included cutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
52
4
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 37 publications
16
52
4
2
Order By: Relevance
“…The most significant identifier of work disability in patients with RA has been shown to be the HAQ functional disability score. 26,27 These findings, combined with those of the present report, suggest that functional disability may be closely linked to the improvement of productivity but not to the disease activity of RA at baseline.…”
Section: Discussionsupporting
confidence: 59%
“…The most significant identifier of work disability in patients with RA has been shown to be the HAQ functional disability score. 26,27 These findings, combined with those of the present report, suggest that functional disability may be closely linked to the improvement of productivity but not to the disease activity of RA at baseline.…”
Section: Discussionsupporting
confidence: 59%
“…The precise mechanisms underlying the high prevalence of these clinical manifestations remain to be further investigated. [24][25][26] There is no single laboratory examination specific for the diagnosis of NPSLE. [27][28][29][30][31] We found that most patients presented with positive ANA, lower levels of serum C3, abnormal erythrocyte sedimentation rate, and higher levels of serum IgG as well as abnormal cranial MRI brain imaging, similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,8 Some authors have found an association between NPSLE and low serum levels of C3 and C4 complement components, while increased levels of these proteins and the soluble form of C5b-9 have been found in the cerebrospinal fluid (CSF) of SLE patients. [9][10][11] An enhanced deposition of complement activation products on platelets has also been associated with the development of thrombosis in SLE, a process in which antiphospholipid antibodies (aPL) have been reported to notably collaborate. 12,13 In murine models, both deletion of factor B, a key alternative pathway protein, and inhibition of the classical and alternative complement cascade with the complement inhibitor Crry, demonstrated to alleviate experimental CNS lupus.…”
Section: Introductionmentioning
confidence: 99%